2002
DOI: 10.1159/000065873
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Haemodialysis Improves the Response to Hepatitis B Virus Vaccination

Abstract: Background: As patients on chronic haemodialysis (PCHD) elicit a weaker response to vaccination with recombinant hepatitis B virus surface antigen (HBsAg), we conducted this study to see how dialysis efficacy affects response to hepatitis B virus (HBV) vaccination. Methods: Study subjects consisted of 30 PCHD. All subjects were vaccinated with 4 × 40 µg HBsAg i.m. at 0, 1, 2, and 6 months. If a subject had an HBsAg antibody (HBsAb) level <10 IU/l after vaccination, he or she received a booster dose. Subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…In their observational study on 105 patients on maintenance HD, Eardley et al [33] observed no significant difference in mean rHuEPO dose between responder and non-responders dialysis patients after a primary course of vaccine [6,495 vs. 6,171 IU/week (p = 0.66)]. Identical results were obtained by Kovacic et al [34]. No link between seroresponse rate and rHuEPO therapy, as assessed by rate of rHuEPO administration between responder and non-responder patients, was noted after the HBV vaccine schedule in another cohort study [35].…”
Section: Discussionmentioning
confidence: 73%
“…In their observational study on 105 patients on maintenance HD, Eardley et al [33] observed no significant difference in mean rHuEPO dose between responder and non-responders dialysis patients after a primary course of vaccine [6,495 vs. 6,171 IU/week (p = 0.66)]. Identical results were obtained by Kovacic et al [34]. No link between seroresponse rate and rHuEPO therapy, as assessed by rate of rHuEPO administration between responder and non-responder patients, was noted after the HBV vaccine schedule in another cohort study [35].…”
Section: Discussionmentioning
confidence: 73%
“…We could assume that inefficient dialysis and longer duration of dialysis weakened the immune response further, resulting in a poor immune response. Previously, Kovacic et al [17] reported that efficient HD significantly improves the response to hepatitis B vaccination. These authors showed that good responders had a better Kt/V than poor responders.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatitis B antibody response rate had also been shown to diminish with increasing severity of renal failure [14, 15] and ineffective dialysis [16]. Thus, one of the plausible reasons for the lower response rate among the overweight subjects could have been related to their inadequate dialysis, in particular with majority of them undergoing peritoneal dialysis.…”
Section: Discussionmentioning
confidence: 99%